Kesan drama hibur-didik dan dokumentari dalam mempengaruhi niat untuk menderma organ: satu eksperimen berteraskan model Elaboration Likelihood - Ghazali, Suraini; Mustafa, Hasrina; Omar, Bahiyah (Penerbit UKM, 2014)
The study aimed to examine the differential effects of watching edutainment and documentary videos on the viewers’ intention to donate organ. This study used the Elaboration Likelihood Model developed by Petty and Cacioppo (1986) to investigate the process of persuasion in both edutainment and documentary exposure conditions. Using an experimental research method, the study also explored the effect of three different times’ exposures: pre, post and follow-up (after one-month) on the viewers’ intention to donate organ. A total of 164 participants were recruited to participate in this study and they were randomly assigned to the two treatment groups; the edutainment video group and the documentary video group. Statistical analyses used in this study were Pearson Correlation Coefficients, Multiple Regression and One Way Repeated Measure ANOVA with Post-Hoc test. The results of the study supported the premises of the Elaboration Likelihood Model which showed that the persuasive process in the edutainment group was associated with the peripheral route (i.e: a process which was not mediated by counter arguing and reactants), while the process in the documentary group was associated with the central route (i.e: a process which was mediated by counter arguing and reactants). The study also found that participants in the documentary group were more incline towards donating their organs than those in the edutainment group which further contested on the previous claims on the effectiveness of edutainment in the process of persuasion.